CORRELATION OF VOCABULARY MASTERY TOWARDS STUDENTS’ SPEAKING SKILL - Fitriyeni Fitriyeni (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2021)
Communication is a significant skill for students to be mastered because it is related to their skills in producing sounds and expressing their opinions using linguistics and sociolinguistics competences. To improve speaking skill, the students should have good knowledge and understanding of vocabularies that they could use to build words and sentences based on the language contexts. This research conducted to find out whether there is a correlation between students’ vocabulary mastery and students’ speaking skills, and the method used is descriptive quantitative using the statistic analysis SPSS 20. The participant of this research is ten grade students of SMK MANBAUL KHAIR in the first semester 2019/2020 academic year. The research finds that there is a positive correlation between the students’ vocabulary mastery and students’ speaking skills. Although the correlation is low, calculated r = 0.394, it is still considered that this correlation is positive, that means teachers should give the students related meaningful materials to build their vocabularies and provide the opportunity for the students to practice using their new vocabularies.